Some Considerations in the Translation of African Drama - Che Suh, Joseph (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThis paper examines the types of African drama South of the Sahara. It illustrates and underscores the fact that each of the numerous sub-categories found in that part of the continent has its own distinctive characteristics which the translator must actively identify and map onto the target text.